2021
DOI: 10.3389/fpubh.2021.772376
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time We Stop Discouraging Evening Physical Activity? New Real-World Evidence From 150,000 Nights

Abstract: Professional and colloquial sleep hygiene guidelines advise against evening physical activity, despite meta-analyses of laboratory studies concluding that evening exercise does not impair sleep. This study is the first to investigate the association between objectively measured evening physical activity and sleep within a real-world big-data sample. A total of 153,154 nights from 12,638 individuals aged 18–60 years (M = 40.1 SD = 10.1; 44.5% female) were analyzed. Nighttime sleep and minutes of physical activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In contrast, sleep quality was not affected by PA levels in the preceding day. This finding echoes our previous report from this same dataset, showing that MVPA performed during the evening hours before bedtime was unrelated with sleep quality [22]. However, there have been very few studies that have found better sleep quality (i.e., sleep efficiency) to precede such high levels of PA [6].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, sleep quality was not affected by PA levels in the preceding day. This finding echoes our previous report from this same dataset, showing that MVPA performed during the evening hours before bedtime was unrelated with sleep quality [22]. However, there have been very few studies that have found better sleep quality (i.e., sleep efficiency) to precede such high levels of PA [6].…”
Section: Discussionsupporting
confidence: 87%
“…However, comparing the results is challenging, as the studied variables, intensity of PA, and study design varied. In addition, timing of the physical activity may matter-we have previously reported from this same data set that MVPA performed in the 3hbefore bedtime was associated with slightly longer sleep duration [22].…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, a synergistic health effect has been documented of physical inactivity and poor sleep on the development of metabolic syndrome and increased mortality 175 , 176 . Findings also suggest that evening physical activity should be discouraged owing to a disturbance of night-time sleep; however, any effect here is likely to be small 177 . Of note, whether being physically active helps to prevent or reduce the metabolic health consequences of insufficient sleep and circadian misalignment is unknown.…”
Section: Potential Strategies To Improve Sleepmentioning
confidence: 81%
“…Thus, studying the reciprocal associations between the circadian clock and exercise performance is of growing interest. Research on PA in relation to sleep has mostly focused on the timing, duration, and intensity of PA with the overarching goal to optimize beneficial outcomes for the individual’s health and wellbeing ( Kahn et al, 2021 ; Lang et al, 2022 ). The timing of PA can alter rest–activity profiles, and affect clock gene expression.…”
Section: Introductionmentioning
confidence: 99%